Estudio de la calidad del producto en el primario 53C de la subestación 53 de la EEQ - Maula Maula, José Arnulfo (2012)
We present the main technical features of the system of Quito Electric Company, such as its concession area, relevant data, infrastructure, power generation, distribution substations, transmission lines and sub-transmission, types distribution networks, customer classification, the characteristics of the substation No. 53, the existing primary and 53C primary purpose of this study. Presents the results of the selection of the sample, to determine the number of transformers of the 53 primary, in which were made measurements, using the analyzer industrial also presents the results of lifting the load installed in the selected sample and results of monitoring quality of the product in transformers to the distribution network in the established sample. In addition, comparisons are presented of the results the measurements with the parameters of the regulation of CONELEC-004/01, related to product quality: voltage level, power factor and disturbance voltage to determine if the sample meets the quality standards set by the regulator. Technical studies are included and results that support the selection of equipment needed to overcome the failings of the parameters of product quality, and includes the details and specifications of this equipment, and the results of economic evaluations that identify the feasibility of implementing the selected equipment. Finally, conclusions and recommendations are given.